The Rape Myth Questionnaire – A Pilot Study - Genc, Ana; Samac, Nikola; Knežević, Lara; Petrović, Kristina; Konc, Iva (Psihološka istraživanja, 2018)
Rape myths are distorted beliefs about rape (its causes, context, consequences, perpetrators, victims and their interaction). Rape myths serve to deny, trivialize or justify this form of sexual violence and they contribute to frequently intolerant and hostile treatment of rape victims. Sincethis phenomenonhas not yet received the attention it deserves in the framework of national science,the main aimof this pilot study was to develop a questionnaire in the Serbian language which measures rape myth acceptance. The current paperpresents the newly designed Rape Myth Questionnaire, its factor structure, as well as the psychometric characteristics of the scale. The second aim of the study was tomap of the prevalence of rape myth acceptance in Serbia. The survey was conducted on a sample of 482 respondents. The results indicate that the Rape Myth Questionnaireisa reliable instrument, with highly valid and representative items. The questionnaire proved to be unidimensionalon the sample used in the study. The Discussion contains a detailed description of the prevalence of different groups of rape myths in our country.